Patellar Dislocation Patients Had Lower Bone Mineral Density and Hounsfield Unit Values in the Knee Joint Compared to Patients with Anterior Cruciate Ligament Ruptures: A Focus on Cortical Bone in the Tibia - Yue Wu; Yiting Wang; Haijun Wang; Shaowei Jia; Yingfang Ao; Xi Gong; Zhenlong Liu (Bioengineering)
Anterior cruciate ligament (ACL) rupture and patellar dislocation (PD) are common knee injuries. Dual-energy X-ray absorptiometry (DXA) and computed tomography (CT) are widely used clinical diagnostic tools. The aim was to investigate the characteristics of knee bone mineral density (BMD) in patients with ACL rupture and PD and to explore the relationship between BMD and Hounsfield unit (HU) values. This prospective cross-sectional study included 32 ACL rupture and 32 PD patients assessed via DXA and CT. BMD and CT measurements were taken from regions of interest in the femoral and tibial condyles. Statistical analyses included t-tests and mixed-effects models. The results showed that BMD in the PD group was significantly lower than in the ACL group (p < 0.05). The HU values of cortical bone in the femur and tibia differed significantly between the ACL group and the PD group (p < 0.05). The BMD of the femur and tibia showed significant correlations with the HU values of cancellous bone and cortical bone (p < 0.05). The conclusion was that PD patients had lower BMD and HU values in the femur and tibia compared to patients with ACL ruptures, particularly in the cortical bone of the tibia, and there was a strong correlation between HU value and BMD.